Dialogue instead of a monologue : advertisers' expectations towards the media - Tolvanen, Kristiina (2011)
Stakeholders’ expectations can define the future of the media. Due to advertising revenues, producing audiences desirable for advertisers has been considered as a central function of media. Furthermore, it has been claimed that mass media today would not exist without advertisers. If media organizations want to survive, they will have to acknowledge the expectations that their stakeholders such as advertisers have towards them in the new media environment. Even though meeting stakeholders’ expectations can be crucial for an organization’s future in terms of legitimacy and reputation, expectations have been an understudied topic in organizational communication.